The contribution of fiber components to water absorption of wheat grown in the UK. Issue 5 (16th July 2020) - Lovegrove, Alison; Wood, Abigail J.; Hassall, Kirsty L.; Howes, Liz; Poole, Mervin; Tosi, Paola; Shewry, Peter
Abstract: Background and objectives: The water absorption (WA) of white wheat flour is a major factor affecting processing quality, and millers, therefore, process their wheat to achieve the required level. Although it is likely that WA is determined by the amounts and compositions of three major grain components, starch, protein, and arabinoxylan, the contribution of the latter is not agreed and not recognized in the widely used Farrand equation. Findings: We have measured a range of parameters related to fiber amount and composition and tested the ability of these to improve the prediction of WA using a modified Farrand equation. The addition of a range of single fiber traits improved the prediction of WA from a baseline of 82.98% to a maximum of 86.78%, but inclusion of all fiber traits as PCs resulted in a further improvement to 90%. Inclusion of the PCs also accounted for variation in WA between harvest years. The greatest improvement from inclusion of a single trait was observed with β‐glucan, the inclusion of arabinogalactan peptide (AGP) also resulted in improved prediction of WA. Conclusions: The study shows that fiber components contribute to variation in WA, including differences between harvest years, but that β‐glucan and AGP have similar or greater impacts than AX. Significance and novelty: The study dissects the contributions of AX amount and composition to WA and demonstrates a contribution of b‐glucan for the first time.